Edukasi Pengenalan Jentik Aedes aegpty Pada Anak dengan Pendekatan DAI (Dongeng Anak Islam) di SDN 5 Guntung Manggis Kota Banjarbaru. - Agustina, Norsita (Jurnal BALIRESO, 2019)
In the city banjarbaru especially to urban villages Guntung Manggis is a endemicdengue feverdangue.And the data on the last year of 2018 began to provide support to the moon januari-agustusthere have been cases 20 a case that affected dengue fever dangue.In early august 2018, of denguefever reach 5 people and 2 people in whom dieddengue fever danguein the area was quite highespecially in under-fives and school age.Based on survey.At state elementary school 5 GuntungManggis is by 12 students dengue fever within 3 months. So that education is required recognitionaedes mosquito larvae aegpty in order to solve the problems of dengue fever in the neighborhoodthese schools. Objectives of the activities it is will increase people awareness schools fromstudents, teachers and parents in handling the larva mensukseskan eradication aegpty so thedengue fever can be reduced in the rainy especially. Methods used fairy tale is education islamistkid with the title of the kingdom of mosquitoes attack humans and the formation of detective boysexterminator aegpty aedes mosquito larvae. The results of this public service activities is theincreased knowledge about disease dengue feverAnd the behavioral changes in leg up on thehandling of the eradication of aedes mosquito larvae aegpty for the entire school independently.